PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN SACOM ENERGIA LDA - Aswar, Tasya Arsita; Army, Widya Lelisa; Partimah, Partimah (Jurnal EBI, 2024)
SACOM Energia Lda is an East Timorese company operating at the oil gas industry. Development of business competencies requires integrated human resource management (HRM) in an institute. The research purpose is to evaluate and elaborate factors that have influence of employee performance such as rewards and punishments. Data were  obtainedfrom SACOM Energia Lda employees using a questionnaire method. All the data calculated using SPSS program. Tests carried out include validity, reliability, normality, multicollinearity, and heteroscedasticity, each test carried out obtained acceptable. Based on statistic analysis, it was discovered that the provision rewards, punishments, and performance were quite good with values of 34.2, 40.8, and 33.9, respectively. The partial test results show that the tcount ttable on both variables and the sig value 0.05, then both hypotheses H1 and H2, on variables (X1) and (X2) are proven to have an effect and according to simultaneous test, it was found that the sig value is less than 0.001, this shown the result indicate the variables (X1 X2) simultaneously will affect employee performance, the result H3 hypothesis is proven to have an effect. This research can be concluded that rewards and punishment have an influence of 50,4% on performance, while 49.6% is caused by external factors.Keywords: Human Resource Management, Rewards, Punishment, EmployeePerformance.